2010
DOI: 10.1111/j.1755-5922.2010.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Individualised Assessment of Response to Clopidogrel in Patients Presenting with Acute Coronary Syndromes: A Role for Short Thrombelastography?

Abstract: SUMMARYIntroduction: There is considerable interindividual variation in response to the antiplatelet agent clopidogrel. Hyporesponse predicts negative outcomes in patients presenting with a variety of ischemic cardiac conditions and following intracoronary stent placement. Many tests of clopidogrel activity are time consuming and complex. Short thromboelastography (s-TEG) allows rapid measurement of platelet clopidogrel response. Aims: We initiated this study to investigate the utility of s-TEG in assessing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…13 The AUC15 TEG method, known as short TEG, has been well validated by this group and is described in detail elsewhere. [12][13][14][15][16]18,19 Recent data from this group 12,14 has shown that the novel parameter AUC15 is not only easily reproducible with minimal intraindividual and interindividual variability but also correlates well with VerifyNow in the assessment of responses to antiplatelet therapy (AUC15 AA Channel and VerifyNow aspirin response units, correlation coefficient r = 0.701; P , 0.001; and AUC15 ADP channel and VerifyNow P2Y12 reactivity units, correlation coefficient r = 0.609, P , 0.001). 12 In this study, platelet reactivity and response to clopidogrel was determined from AUC15 of the ADP channel.…”
Section: Blood Sampling and Short Teg Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…13 The AUC15 TEG method, known as short TEG, has been well validated by this group and is described in detail elsewhere. [12][13][14][15][16]18,19 Recent data from this group 12,14 has shown that the novel parameter AUC15 is not only easily reproducible with minimal intraindividual and interindividual variability but also correlates well with VerifyNow in the assessment of responses to antiplatelet therapy (AUC15 AA Channel and VerifyNow aspirin response units, correlation coefficient r = 0.701; P , 0.001; and AUC15 ADP channel and VerifyNow P2Y12 reactivity units, correlation coefficient r = 0.609, P , 0.001). 12 In this study, platelet reactivity and response to clopidogrel was determined from AUC15 of the ADP channel.…”
Section: Blood Sampling and Short Teg Analysismentioning
confidence: 90%
“…Platelet reactivity was measured using a well-validated point-of-care platelet function test known as short thrombelastography (TEG), which has been described in detail elsewhere. [12][13][14][15][16] …”
Section: Introductionmentioning
confidence: 98%
“…It is influenced by platelet function, coagulation factors, natural inhibitors of coagulation and fibrinolysis. Some studies showed that TEG is potentially useful for studying patients on antiplatelet treatment (59)(60)(61)(62)(63)(64)(65)(66).…”
Section: Thromboelastography (Teg)mentioning
confidence: 99%
“…Vasodilator-stimulated phosphoprotein (VASP) is a type of intracellular actin regulatory protein, which is a reaction VASP phosphorylation levels can be determined using flow cytometry to determine the treatment efficacy of clopidogrel in patients (11,12). Previous studies have demonstrated that platelets exhibit high levels of microRNA (miRNA) expression (13,14), which has an important role in the pathology of diseases associated with platelets (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Following transformation by cytochrome P450, the active metabolites of clopidogrel irreversibly bind to the P2Y 12 ADP receptor on the surface of platelets and block the inhibition of cyclic adenosine monophosphate (cAMP) by inhibiting the binding sites of ADP, which promotes cAMP-dependent phosphorylation of proteins. Inhibition of the binding between fibrinogen and platelet glycoprotein GPIIb/IIIa receptor, and the subsequent deactivation of glycoprotein GPIIb/IIIa complexes inhibits the aggregation of platelets (10).…”
Section: Introductionmentioning
confidence: 99%